Population structure and genetic diversity analysis in Sali (Oryza sativa) rice germplasm of Assam using microsatellite markers - Saikia, Sandhani; Handique, Pratap Jyoti; Modi, Mahendra K (ORYZA-An International Journal of Rice, 2021)
Genetic diversity is the source of novel allelic combinations that can be efficiently utilized in any crop improvement program. To facilitate future crop improvement programs in rice, a study was designed to identify the underlyinggenetic variations in the Sali rice germplasms of Assam using SSR markers. The 129 SSR markers that were used in the study amplified a total of 765 fragments with an average of 5.93 alleles per locus. The Shannon's Information Index was found to be in the range from 0.533 to 1.786. The Polymorphism Information Content (PIC) fell into the range from 0.304 to 0.691 with a mean value of 0.55. The overall FST value was found to be 0.519 that indicated the presence of genetic differentiation amongst the genotypes used in the study. The Sali population was divided into two clusters. The information obtained from the present study will facilitate the genetic improvement of Sali rice cultivars.